Nuclear structure theory - Irvine, J. M. (John Maxwell) (International series of monographs in natural philosophy, 1972)
Nuclear Structure Theory provides a guide to nuclear structure theory. The book is comprised of 23 chapters that are organized into four parts; each part covers an aspect of nuclear structure theory. In the first part, the text discusses the experimentally observed phenomena, which nuclear structure theories need to look into and detail the information that supports those theories. The second part of the book deals with the phenomenological nucleon-nucleon potentials derived from phase shift analysis of nucleon-nucleon scattering. Part III talks about the phenomenological parameters used to de.